A self-contained real-time angle deviation detection and measurement technique for straight line quadrocopter navigation using accelerometer / Nor Hashim Mohd Arshad … [et al.] - Mohd Arshad, Nor Hashim; Abdul Razak, Noorfadzli; Adnan, Ramli; Misnan, Mohamad Farid; M. Thamrin, Norashikin (Research Innovation Business Unit, 2014)
Deviation from a planned path due to dynamic wind disturbances could defect a quadrocopter navigation accuracy and thus may result in poor execution of a task. Few researchers have proposed correction algorithms to be integrated in an autonomous quadrocopter navigation system to avert the problem. The algorithms are not practically applicable to allow a quadrocopter to navigate precisely on a planned trajectory around a small area with the presence of dynamic disturbances. This project proposes a new real-time adaptive trajectory correction algorithm for quadrocopter, which could specifically detect angle deviation through the use of accelerometer to allow for corrective action.